(untitled) (World Economics and Finance Bulletin, 2024)
This article examines the development of business entities within small industrial zones, focusing on the factors that contribute to their growth and the challenges they face. Small industrial zones, often characterized by their specialized focus on specific industries or sectors, have emerged as pivotal platforms for nurturing small and medium-sized enterprises (SMEs) and fostering economic development. Through a comprehensive review of literature and case studies, this study identifies key drivers of success, including access to infrastructure, financial incentives, regulatory support, and the role of innovation and technology. Additionally, the article delves into the obstacles encountered by businesses in these zones, such as financing difficulties, regulatory hurdles, and market competition. The analysis further explores the impact of governmental policies and support mechanisms on the sustainability and expansion of businesses in small industrial zones. By drawing on examples from various regions, the study provides insights into best practices and policy recommendations to enhance the effectiveness of small industrial zones as engines of economic growth. The findings underscore the importance of a holistic approach that includes stakeholder collaboration, tailored support services, and adaptive regulatory frameworks to ensure the thriving development of business entities in these zones.